Zambia cervical cancer control program resource mapping – Leveraging support to achieve the 90-70-90 elimination target. (June 2021) - Lombe, Dorothy; Msadabwe, Susan; Maka, Mbaita; Samboko, Memory; Haimbe, Prudence; Sichamba, Samuel; Chanda, David; Choobe, Namwiinga; Banda, Patrick; Simwenda, Maureen; Chaila, Mwate Joseph; Kamfwa, Paul; et al.
Highlights: Policy cohesiveness is important to achieve developmental goals. Resource mapping is necessary in a multi-funded environments. Investment must be concurrent in the care continuum for cervical cancer elimination. Abstract: Background: Zambia has one of the highest incidence and mortality rates of cervical cancer at 65.5 and 43.4 per 100 000 respectively. In line with efforts of the cervical cancer elimination strategy the Zambia national cervical cancer sub-committee undertook a resource mapping exercise of projected spending on the prevention and control program. The aim was to elicit the available resources over a prospective 4-year period and compare it to the projected costs. Materials and methods: A 4-step approach was used for this activity. This included creation of tool adapted for the local program, orientation of stakeholders to the tool, population of the tool by stakeholders and collation, comparison and reporting of submitted data. Comparative analysis to the cervical cancer control costing report 2019–2023 was conducted. Results: Fifty-nine percent of resources in the stipulated period were allocated to prevention efforts. Isolated with diagnostic, treatment and palliation (14 %) the prevention allocation increased to 81 %. Community and stakeholder engagement was 5 % whilst technical assistance and health information were 12 % and 9 % respectively. The dispensation to research was the lowest at 0.7 %. For health system levels, secondary and primary levels were projected at 40 % and 12 % respectively following the central allotment of 45 %. Community and stakeholder engagement took up 3 %. The secondary prevention to tertiary intervention ratio was 4:1 in the projection compared to approximately 2:1 in the actual budgeted costs for the same period, showing a two-fold discordance. Conclusion: To achieve the accelerated elimination of cervical cancer as a public health problem policy cohesiveness is necessary. This can be facilitated with continuous stakeholder involvement in planning, implementation and review. Policy summary: In order to accelerate the elimination of cervical cancer as a public health problem policy cohesiveness is vital and this can be achieved by continuous stakeholder involvement in planning, implementation and review.